2016
DOI: 10.1021/acssuschemeng.6b00317
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Self-Assembly Mechanisms in the Colloidal Synthesis of Iron Titanate Nanocomposite Photocatalysts for Environmental Applications

Abstract: Colloidal synthesis of iron titanate-based nanocomposites exploiting the interaction of solutions of binary oxide nanoparticles, Fe2O3 and TiO2, was investigated with respect to the pH of the reaction medium and the conditions used for the synthesis of the reactants. It has been demonstrated that while the phase composition of the products is rather analogous, involving the formation of iron titanate phases on the grain boundaries of the binary oxide particles, the morphology of the resulting aggregates can be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 42 publications
5
25
0
Order By: Relevance
“…The value of the band gap for TiO 2 was 3.28 eV. This value is in good agreement with the data presented in previous works, 26,42 where it was found that the E g value is determined by the synthesis method.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The value of the band gap for TiO 2 was 3.28 eV. This value is in good agreement with the data presented in previous works, 26,42 where it was found that the E g value is determined by the synthesis method.…”
Section: Resultssupporting
confidence: 92%
“…The obtained values are in agreement with the published data for low concentrations of doping elements. 22,24,27,42,43 E g ¼ 1240 l :…”
Section: Resultsmentioning
confidence: 99%
“…This could be due to the difficulty of obtaining pure phases. In some studies the sol‐gel method was applied to prepare iron‐doped titanium oxides and iron titanates under different preparative conditions, including the use of surfactants or other organic compounds to control their textural properties, and through multi‐step synthesis . In the present study, a straight‐forward sol‐gel preparation route that does not involve any surfactant resulted in Fe(III)‐Ti(IV) mixed oxides with interesting textural and chemical properties.…”
Section: Introductionmentioning
confidence: 78%
“…X-ray diffraction patterns approved the presence of pseudobrookite, rutile, hematite, and Fe 2 Ti 2 O 7 phases at 950 °C. The interaction of binary oxide nanoparticles, Fe 2 O 3 ,and TiO 2 in the ratio of 1:1 or 2:1 using the different synthesis pathways employed to obtained Fe 2 Ti 2 O 7 or Fe 2 TiO 5 , respectively, in order to investigate the photocatalytic activity of heterostructures was reported [11]. The crystallization of pseudobrookite, landauite, anatase, and even hematite took place over reported conditions.…”
Section: Resultsmentioning
confidence: 99%
“…It is shown that the relationship of the structure and properties of the materials, as well as the dependence on the preparation conditions and enhanced photocatalytic activity for the decomposition of organic dye. The materials demonstrated the high photocatalytic activity comparing with iron titanates produced by conventional techniques with strong magnetic separation properties [11]. As known from literature, the synthesis of iron titanates, Fe 2 Ti 2 O 7 , Fe 2 TiO 5 , FeTiO 3 , or others, can be achieved by ceramic or sol-gel technique [912].…”
Section: Introductionmentioning
confidence: 99%